Immobilization of Cerium(IV) Oxide onto Reduced Graphene Oxide in Epoxy Resin Matrix as Radar Absorbing Composite for X-band Region - Bolilanga, Patricya Inggrid Wilhelmina; Basuki, Rahmat; Apriliyanto, Yusuf Bramastya; Prasojo, Agus Eko; Lazuardy, Ardyan; Anitasari, Reza; Putri, Riyanti; Sasongko, Nugroho Adi; Santiko, Arief Budi (Indonesian Journal of Chemistry, 2024)
The rGO/CeO2/epoxy composite has been successfully prepared as radar absorbing material (RAM) for the X-band (8–12 GHz) region. The reduced graphene oxide (rGO) originated from pencil graphite oxide (GiO) was synthesized through the modified Hummer method. The synthesis of rGO/CeO2/epoxy was conducted by immobilization of cerium(IV) oxide into rGO (rGO/CeO2) via hydrothermal method and followed by composited the rGO/CeO2 with epoxy resin matrix. Morphological analysis by SEM-EDX indicates that the rGO/CeO2 structure appears to be a tangled layer of edges randomly aggregated, and CeO2 is uniformly anchored on the rGO surface. From the diffractogram result of the XRD instrument, rGO exhibits changes in crystallinity, indicating a transformation of the interlayer structure from multilayer GiO to a single layer of rGO. The presence of Ce–O was indicated at wavenumber 553 cm−1 of rGO/CeO2 by FTIR. The microwave absorbing performance of rGO/CeO2/epoxy conducted by vector network analyzer (VNA) showed that the RL value of the composite was −3.22 dB (47% of electromagnetic wave absorption) at a frequency of 9.25 GHz at the thickness of 1 mm composite. The composite has the promising prospect of being developed as a captivating candidate for the new type of microwave absorptive materials.